Ensino médio em rede: uma proposta de formação continuada para os professores do ensino médio da rede pública estadual de São Paulo - Silva, Amélia dos Santos (2010)
This research aimed to study the Programa Ensino Médio em Rede - a continuing education program for high school teachers from public state of Sao Paulo - trying to understand the extent to which he helped the teacher in making the curriculum changing market conditions, this level of education and in their daily practice. The study was conducted in a qualitative approach. For this I used as tools document analysis and structured interviews with the teachers participating in this Programa, to investigate the possible scope of a continuing education course in teaching. This research was possible to understand the changes that proclaimed by the Programa became part of everyday practical experiences in the school through the reflections and actions played out by teachers during the course. Positive aspects of Ensino Médio em Rede was appointed the relationship between teachers, the quality of teaching material and the fact that the course occurred in the school environment in which participants worked. On the negative side were highlighted insufficient time for development activities, as well as the lack of infrastructure and equipment required for some of the proposed study. The research found out also the lack of coordination between the public policies of teacher education and the practical reality of the school and it raised one aspect that has hindered the work in high school: the lack of a clear definition of its purposes